Recent advances on thermosensitive hydrogels-mediated precision therapy - Hao Chen; Jiangmei Xu; Jiangwei Sun; Yongxin Jiang; Wang Zheng; Wei Hu; Haisheng Qian (Elsevier, 2024)
Precision therapy has become the preferred choice attributed to the optimal drug concentration in target sites, increased therapeutic efficacy, and reduced adverse effects. Over the past few years, sprayable or injectable thermosensitive hydrogels have exhibited high therapeutic potential. These can be applied as cell-growing scaffolds or drug-releasing reservoirs by simply mixing in a free-flowing sol phase at room temperature. Inspired by their unique properties, thermosensitive hydrogels have been widely applied as drug delivery and treatment platforms for precision medicine. In this review, the state-of-the-art developments in thermosensitive hydrogels for precision therapy are investigated, which covers from the thermo-gelling mechanisms and main components to biomedical applications, including wound healing, anti-tumor activity, osteogenesis, and periodontal, sinonasal and ophthalmic diseases. The most promising applications and trends of thermosensitive hydrogels for precision therapy are also discussed in light of their unique features.